A case study of Singapore Management University Libraries: Adopting a mixed methods approach towards collection evaluation - LIM, Samantha Li Min (Institutional Knowledge at Singapore Management University, 2021)
With rising costs and limited resources, it has become increasingly important for academic libraries to make acquisition decisions prudently to build a collection that meets its users' learning, teaching, and research needs. As such, Singapore Management University's (“SMU”) Libraries use a patron-driven acquisitions process, whereby acquisition decisions are guided by users' needs and requests. This article seeks to investigate if the current patron-driven acquisitions approach adequately meets the research needs of SMU's users through a mixed methods approach. A collection analysis was first conducted on the SMU Libraries' publications' references from the years 2017 to 2018 using the Scopus database. To ensure that the results of the study were valid and reliable, this study also analysed the Library Service Quality Survey for 2018, in addition to interviews with selected undergraduate and postgraduate students. This resulted in the triangulation of these results enabling comparison and analysis across a range of dimensions. The findings show that the library collection was largely able to meet users' needs. Most of the cited publications could be found in the library collection, and users were satisfied with the collection. However, there was a lack of awareness of library resources and how to use them effectively.